Blocking GPR15 Counteracts Integrin-dependent T Cell Gut Homing in Vivo - Schramm, Sebastian; Liu, Lijuan; Saad, Marek; Dietz, Lisa; Dedden, Mark; Müller, Tanja; Atreya, Imke; Bosch-Voskens, Caroline; Atreya, Raja; Neurath, Markus; Zundler, Sebastian (Journal of Crohns & Colitis, 2024)
Background and Aims: The G protein coupled receptor GPR15 is expressed on and functionally important for T cells homing to the large intestine. However, the precise mechanisms by which GPR15 controls gut homing have been unclear. Thus, we aimed to elucidate these mechanisms as well as to explore the potential of targeting GPR15 for interfering with T cell recruitment to the colon in inflammatory bowel disease [IBD]. Methods: We used dynamic adhesion and transmigration assays, as well as a humanised in vivo model of intestinal cell trafficking, to study GPR15-dependent effects on gut homing. Moreover, we analysed GPR15 and integrin expression in patients with and without IBD, cross-sectionally and longitudinally. Results: GPR15 controlled T cell adhesion to MAdCAM-1 and VCAM-1 upstream of α4β7 and α4β1 integrin, respectively. Consistently, high co-expression of these integrins with GPR15 was found on T cells from patients with IBD, and GPR15 also promoted T cell recruitment to the colon in humanised mice. Anti-GPR15 antibodies effectively blocked T cell gut homing in vitro and in vivo. In vitro data, as well as observations in a cohort of patients treated with vedolizumab, suggest that this might be more effective than inhibiting α4β7. Conclusions: GPR15 seems to have a broad, but organ-selective, impact on T cell trafficking and is therefore a promising target for future therapy of IBD. Further studies are needed.
CRIS-Team Scopus Importer:2024-08-16
Keywords: adhesion; GPR15; Inflammatory bowel disease; T cell homing; vedolizumab